Kesiapan Implementasi E-Government Pada Badan Pengelolaan Keuangan Dan Aset Daerah (BPKAD) Pemerintah Provinsi Sulawesi Selatan - Maidah Maidah (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study aims to determine and analyze the level of readiness for e-government implementation at the Regional Financial and Asset Management Agency of the South Sulawesi Provincial Government. The research method used is a qualitative research method with a descriptive qualitative approach to determine how e-government implementation at the Regional Financial and Asset Management Agency of the South Sulawesi Provincial Government. The analytical methods used consist of data collection, data reduction, data presentation, and drawing conclusions. The results of the study categorize e-government implementation at the Regional Financial and Asset Management Agency (BPKAD) of South Sulawesi Province as quite ready but not yet optimal. Key advantages include core applications (SIMAKDA, SIPD, and SIMBADA) that are relatively easy to use, an official portal that provides information transparency, and support and incentives for employees to improve their ICT skills. However, many challenges remain. These include misaligned policies at the central and regional levels, a shortage of IT personnel, network instability in some OPDs, and inadequate data security systems. These conditions cause problems such as delays in digital public services, low data integration efficiency, cybersecurity risks, and problems in maintaining service sustainability. Therefore, to enable BPKAD to achieve more efficient, secure, and sustainable digital government standards, improvements in infrastructure, regulations, and human resource capacity are required.